PENDIDIKAN ISLAM MASA PENJAJAHAN BELANDA DAN JEPANG - Legimin, Legimin; Aslan, Aslan (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The history of the Indonesian nation's journey, cannot be separated from the role of the Muslim community, especially in the struggle to expel invaders from the face of the Indonesian earth. Through the education sector, Islamic leaders established Islamic education to strengthen the foundations of religion and for the people to fight the education system brought by the Dutch colonialists. The Islamic education system is the only formal education that has its own system and management which is different from the education system brought by the Netherlands. The Dutch government regulations that are so strict and harsh on the activities of madrassas and Islamic boarding schools in Indonesia, do not make Islamic education paralyzed and in ruins. On the other hand, the spirit of Islam was still well preserved, where the ulama and kyai were non-cooperative with the Dutch and they moved away from places close to the Dutch. Similar pressure was experienced by the Islamic education system during the Japanese education era. Where the Japanese government requires teachers to learn Japanese and obliges the Tenno (Emperor) to respect. The strength of the principles of Islamic educator leaders has shown the ability of Islamic education to survive in accordance with Islamic principles, without the influence of any power that is in power.